Wait Time for Endoscopic Evaluation at a Canadian Tertiary Care Centre: Comparison with Canadian Association of Gastroenterology Targets - Derek Yu; Wilma M Hopman; William G Paterson (Canadian Journal of Gastroenterology)
BACKGROUND: In recent years, there has been considerable concern regarding wait times for Canadian health care, which led the Canadian Association of Gastroenterology (CAG) to develop specific wait time targets.